2012
DOI: 10.1007/s13277-012-0527-8
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Skp2 inhibits the growth and metastasis of gastric cancer cells in vitro and in vivo

Abstract: S-phase kinase-associated protein-2 (Skp2) is overexpressed in human cancers and associated with poor prognosis. Skp2 acts as an oncogenic protein by enhancing cancer cell growth and tumor metastasis. The present study has demonstrated that small hairpin RNA (shRNA)-mediated downregulation of Skp2 markedly inhibits the viability, proliferation, colony formation, migration, invasion, and apoptosis of human gastric cancer MGC803 cells, which express a high level of Skp2. In contrast, Skp2 shRNA had only a slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 40 publications
3
34
0
Order By: Relevance
“…Skp2, S-phase kinase-associated protein 2; si, small interfering. ubiquitin-protein ligase complex which regulates the progression of the cell cycle by degrading the tumor suppressor gene p27 kip1 in a ubiquitin-mediated manner (17,18,(33)(34)(35). In the present study, the effects Skp2 depletion by RNAi on cell cycle progression in colon cancer cells were also identified.…”
Section: Discussionmentioning
confidence: 60%
“…Skp2, S-phase kinase-associated protein 2; si, small interfering. ubiquitin-protein ligase complex which regulates the progression of the cell cycle by degrading the tumor suppressor gene p27 kip1 in a ubiquitin-mediated manner (17,18,(33)(34)(35). In the present study, the effects Skp2 depletion by RNAi on cell cycle progression in colon cancer cells were also identified.…”
Section: Discussionmentioning
confidence: 60%
“…Cell migration and invasion assays were performed as previously described (18). For the migration assays, 2.5x10 4 cells suspended in 500 µl serum-free RPMI-1640 medium were seeded in BD Falcon cell culture inserts (8-µm pore; BD Biosciences, San Jose, CA, USA).…”
Section: Reverse Transcription-quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
“…A gelatin zymography assay was performed as previously described (18). Cells (30.0x10 4 ) were seeded in 6-well plates and starved with serum-free medium for 24 h. The conditioned medium was collected and ultracentrifuged.…”
Section: Reverse Transcription-quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
“…MMP family members, which tumor cells secrete, can degrade all of the important extracellular matrix components. Studies have also shown that Skp2-RNAi downregulates MMP-2 (metalloproteinase-2) and MMP-9 (metalloproteinase-9) secretion and inhibits the invasion ability of tumors (25,26).…”
Section: Discussionmentioning
confidence: 99%